Hypolipidemic Effect of Caffeic Acid Isolated From Arctium Lappa Cultivated In Iraq, in Hyperlipidemic Rat Model - Mohammed A. Taher; Dhuha A. Abdul- Hussain; Huda F. Hasan; Zena M. Fahmi; Oday K. Luaibi; Mezaal G. Ali (College of Pharmacy University of Baghdad, 2018)
The goal of the extant revision was to explore the influence of  caffeic acid (CA) extracted from Arctium lappa L. on lipid profile and histology of aorta  in rats .  Analytical study demonstrated a high percentage of both chlorogenic and caffeic acid in the 80 % methanol extract of the aerial parts (leaves and stems) of Arctium lappa L. from the family Asteraceace.  Hypolipidemic activity of caffeic acid was studied against cholesterol induced hypercholesterolemia in Wistar albino rats for thirty days. Rats were separated into normal group (A), hypercholesterolemic positive controller group (B). While, the rest three groups (C, D and E) attended as hypercholesterolemic trial groups. Caffeic acid was given verbally at doses of 20 mg / kg body mass in Collection (C), 40 mg/kg in Collection(D) then 20 mg/ kg in collection (E) after two weeks of administration of cholesterol induced hypercholesterolemia. There was an obvious histological improvement of changes induced by hypercholesteremia in aorta. Furthermore, using (CA) at 20mg after 2 weeks of feeding on cholesterol rich diet led to a important decline (P<0.05) in serum whole cholesterol levels in compassion with the control and cholesterol rich diet group. Moreover, There was a great improvement in the histology results convinced by the high cholesterol gorgeous diet, which can partly be attributed to an antioxidant activity of (CA).                           Keywards: Arctium lappa, Caffeic acid , Hypolipidimic, Hypercholesterolemia.